2013
DOI: 10.1007/s00284-013-0436-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Intracellular Bacteria in Adenoid and Tonsil Tissue Specimens: The Efficiency of Culture Versus Fluorescent In Situ Hybridization (FISH)

Abstract: Monocyte/macrophage cells from human nasopharyngeal lymphoid tissue can be a source of bacteria responsible for human chronic and recurrent upper respiratory tract infection. Detection and characterization of pathogens surviving intracellularly could be a key element in bacteriological diagnosis of the infections as well as in the study on interactions between bacteria and their host. The present study was undertaken to assess the possibility of isolation of viable bacteria from the cells expressing monocyte/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Pharmacodynamic studies in a model of murine lung infection have demonstrated the area under the concentration-time curve-dependent activity and a pharmacokinetic profile that supports further investigation of this compound for the treatment of infections caused by MRSA ( 30 ). The present study adds that gepotidacin may be of particular interest as an agent that acts upon intracellular S. aureus , which may play a critical role in persistent or recurrent skin or respiratory tract infections ( 21 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 86%
“…Pharmacodynamic studies in a model of murine lung infection have demonstrated the area under the concentration-time curve-dependent activity and a pharmacokinetic profile that supports further investigation of this compound for the treatment of infections caused by MRSA ( 30 ). The present study adds that gepotidacin may be of particular interest as an agent that acts upon intracellular S. aureus , which may play a critical role in persistent or recurrent skin or respiratory tract infections ( 21 , 31 , 32 ).…”
Section: Discussionmentioning
confidence: 86%
“…The bacteria have been shown to be located in various anatomical locations in the tonsils and adenoids and have been reported intracellularly 6. In biopsies taken from the middle ear in children with otitis media with effusion, S treptococcus pneumoniae and H. influenzae within biofilms on the tissue surface have been observed 18.…”
Section: Intracellular Bacteriamentioning
confidence: 99%
“…In biopsies taken from the middle ear in children with otitis media with effusion, S treptococcus pneumoniae and H. influenzae within biofilms on the tissue surface have been observed 18. The authors suggest that biofilm-embedded and intracellular pathogens may contribute to the pathogenesis of adenotonsillar hyperplasia 6. However, the localisation of intracellular bacteria is difficult, and only two approaches have so far proved successful.…”
Section: Intracellular Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Культуральными методами не выделяются стрептококки, персистирующие внутриклеточно [21,22]. В исследовании В.Т.…”
unclassified